2019
DOI: 10.18489/sacj.v31i1.587
|View full text |Cite
|
Sign up to set email alerts
|

Towards a framework for online information security applications development: A socio-technical approach

Abstract: The paper presents a validated socio-technical information security (STInfoSec) framework for the development of online information security (InfoSec) applications. The framework addresses both social and technical aspects of InfoSec design. The preliminary framework was developed using a mixed methods research design that collected data from 540 surveys by online banking users and six interviews with online banking personnel. The preliminary framework was presented in another publication and it is bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 23 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…Twenty-nine government officials from agriculture, finance, education, and revenue offices were purposively selected from four districts; Mota, Woreta, Dangila, and Finoteselam, by the Amhara Regional State Science and ICT Commission. A qualitative interpretive approach using semi-structured interviews was used for the requirements elicitation process (see Appendix A) (Mujinga et al, 2019). The data was then transcribed into text and analysed thematically using Atlas.ti8 to identify 9 themes and 17 codes as shown in Table 1.…”
Section: Diagnosismentioning
confidence: 99%
“…Twenty-nine government officials from agriculture, finance, education, and revenue offices were purposively selected from four districts; Mota, Woreta, Dangila, and Finoteselam, by the Amhara Regional State Science and ICT Commission. A qualitative interpretive approach using semi-structured interviews was used for the requirements elicitation process (see Appendix A) (Mujinga et al, 2019). The data was then transcribed into text and analysed thematically using Atlas.ti8 to identify 9 themes and 17 codes as shown in Table 1.…”
Section: Diagnosismentioning
confidence: 99%
“…However, the framework does not provide details such as mechanism for identification of the conflicts, elicitation of suitable trade-offs, dissemination mechanism for usable security patterns; all of which have been considered in the current work. Mujinga et al, (2019) proposed "Socio-technical Information Security Framework". The framework has been designed while considered both technical and social aspects of information security.…”
Section: Related Workmentioning
confidence: 99%
“…Mujinga et al (2019) proposed “Socio-technical Information Security Framework.” The framework has been designed while considering both technical and social aspects of information security. The authors claim that the development of security application can be improved by applying 12 design principles presented in the framework.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In this case, the study professes SM usage into social and technical dimensions, respectively. The social dimension attributes consist of the behavioral (subjective) aspects of information security, while the technical dimension entails the technology (objective) aspects of information security [1] [3] [4]. In line with usable-security principles, no study has been done to identify SM usage information security factors, in the domain of social, and technical dimensions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies often focus on information security attributes associated with mainly the technical aspect of SM usage [5]. And yet, numerous studies have reported social-engineering (behavioral) attacks as one of the prevalent forms of online information security breaches [4] [5]. Therefore, this study was intended to identify, examine, and validate SM socio-technical information security factors, in line with usable-security principles.…”
Section: Introductionmentioning
confidence: 99%